1999
DOI: 10.1183/09031936.99.13612539
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal inflammation in severe glucocorticoid-dependent asthma

Abstract: CD69 surface expression on human lung eosinophils after segmental allergen provocation. P. Julius, W. Luttmann, B. Knoechel, C. Kroegel, H. Matthys, J.C. Virchow Jr. #ERS Journals Ltd 1999. ABSTRACT: CD69 expression on eosinophils is observed in asthma and has been proposed as a marker of eosinophil activation. The role of allergens in the in vivo regulation of CD69 expression on eosinophils, however, remains incompletely understood. It was therefore investigated whether CD69 expression on eosinophils can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
4
22
0
1
Order By: Relevance
“…In a previous study it has been shown that severe asthma is characterized by increased numbers of CD25+ T-cells and relatively low eosinophil counts [11]. Why sensitized T-cells specifically accumulate in the airways of these patients is uncertain.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a previous study it has been shown that severe asthma is characterized by increased numbers of CD25+ T-cells and relatively low eosinophil counts [11]. Why sensitized T-cells specifically accumulate in the airways of these patients is uncertain.…”
Section: Discussionmentioning
confidence: 97%
“…The primary goal of this and previous studies [11] was to investigate whether differences in VCAM expression could account for the differences in inflammatory cell profile between severe and mild asthmatics [11], and the authors therefore specifically selected patients who represented the two extremes of the disease spectrum. Previous studies have already shown that treatment of mild and moderately severe asthmatics with glucocorticoids is associated with a marked depletion of eosinophils and downregulation of T-lymphocyte activation with no differences in the expression of ICAM-1 and E-selectin [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A proportion of these patients is found to be relatively resistant to the anti-inflammatory effects of glucocorticoids as judged by the reduced suppressive effects of dexamethasone on the proliferative response of peripheral blood mononuclear cells (PBMC) to the mitogen phytohaemagglutinin (PHA) [4] and increased peripheral blood T-cell activation [5]. Recently the authors have extended these observations to the bronchial mucosa by demonstrating the existence of increased mucosal T-cell activation in severe glucocorticoid-dependent asthmatics as compared to mild asthma and healthy control subjects [6]. In addition, increased concentrations of free interleukin (IL)-8 have been found in serum of severe asthmatics who were dependent on high doses of inhaled and in most cases systemic glucocorticoids [7].…”
mentioning
confidence: 99%